Analysis of Iron (Fe), Copper (Cu), and Zinc (Zn) on Param Traditional Medicine (Journal of Chemical Natural Resources, 2020)
Param is well known traditional medicine for keeping healthy and treating diseases used by Karo Ethnic groups in North Sumatera. Param is a powder made of various nutritious plants and therefore its contents of the heavy metal were determined by using Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) for qualitative analysis and Atomic Adsorption Spectrophotometry (AAS) for quantitative analysis. The result obtained for the analysis param taken from two samples were 11.814mg/kg and 25.4 mg/kg for Fe, 0.658 mg/kg and 4.536 mg/kg for Cu, and 12.728 mg/kg and 15.184 mg/kg for Zn. Param used as external medicine the content of Fe was 29.36 mg/kg, Cu was 7.368 mg/kg, and Zn was 27.688 mg/kg. The content of all was found in metal, fulfilling the Standart of the Food and Drug Regulatory Agency.